Whereas great inconveniences may take place from our not knowing the number of male inhabitants in each town ... It is resolved, that the selectmen of each town ... shall take the number of all their male inhabitants . ([Printed by Benjamin Edes], 1776)
December 9, 1776 Resolution for towns to take census of males sixteen and older, with some exception.